2005
DOI: 10.1007/s00270-004-2678-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Right Segmental Hepatic Duct Injury Following Laparoscopic Cholecystectomy

Abstract: Successful management of IRSHDI after LC requires adequate identification of the lesion, and multidisciplinary treatment is necessary. Half of the patients can be treated successfully by nonsurgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 14 publications
0
42
0
2
Order By: Relevance
“…Interestingly, the majority of these data advocate surgical intervention. A large proportion of the patients with RPSD injury had eventually experienced late complications in the form of biliary strictures and cholangitic abscesses necessitating further intervention including hepatic resection [10,13,14,19,20]. To the author's knowledge, this report describes the first series promoting the evolving role of nonoperative management for RPSD injury.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, the majority of these data advocate surgical intervention. A large proportion of the patients with RPSD injury had eventually experienced late complications in the form of biliary strictures and cholangitic abscesses necessitating further intervention including hepatic resection [10,13,14,19,20]. To the author's knowledge, this report describes the first series promoting the evolving role of nonoperative management for RPSD injury.…”
Section: Discussionmentioning
confidence: 87%
“…Perini et al [14] reported the second largest series to date. In this series of 12 patients, 8 underwent various surgical reconstruction techniques.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Injuries of the common duct usually require the placement of only one drain, whereas hilar injuries with high-grade strictures of the left and right hepatic ducts or loss of continuity in the ducts require bilateral drain placement [12,13]. Transection or ligation of an aberrant right hepatic duct requires targeted drain placement in the affected segments of the biliary tree [12][13][14].…”
Section: Percutaneous Transhepatic Biliary Drainage Placementmentioning
confidence: 99%
“…The concern of iatrogenic injury in MIS becomes even greater for obese patients because the large layer of peritoneal fat further challenges intraoperative definition of the internal anatomy that is already inherently difficult for MIS. 4 Currently, surgeons operating minimal-invasively do not have an easy-touse, real-time device to aid in intraoperative identification of important anatomic structures that underlie native tissue planes 5 or secondary scar tissues 6 that must be carefully dissected in a stepwise layer-by-layer fashion to avoid injury to these structures. Techniques with a goal of detecting arterial vessels using standalone laparoscopic probes have been a topic of investigation for many years.…”
mentioning
confidence: 99%